Interdisciplinary approach to the correction of pain syndrome in military personnel with post-traumatic stress disorder - Ніколаєва, Олександра; Олександр, Коваленко (Psychosomatic Medicine and General Practice, 2025)
Background: The prevalence of post-traumatic stress disorder (PTSD) and chronic pain among military personnel continues to rise in the context of ongoing combat operations in Ukraine. Chronic pain in this cohort frequently presents with a neuropathic component and is commonly accompanied by symptoms of depression, anxiety, and dissociation. International meta-analyses [Koechlin et al., 2018; Tesarz et al., 2020] highlight the complex pathophysiological interaction between PTSD and pain syndromes, supporting the rationale for combining psychotherapeutic and medical interventions within an interdisciplinary framework. Objective: To evaluate the effectiveness of an interdisciplinary approach in reducing pain intensity, PTSD symptoms, and the risk of pain chronification. Materials and Methods: A single-group prospective pre–post study was conducted with 30 military personnel aged 22–60 years. All participants suffered from chronic neuropathic low back pain with comorbid PTSD symptoms. The medical intervention included facet joint or nerve root injections of betamethasone combined with a local anesthetic. During the following week, patients underwent a short-term psychotherapeutic program comprising one psychoeducational session, 4–5 individual cognitive-behavioral therapy sessions, and one group intervention focused on relaxation techniques. Outcomes were assessed using the Visual Analogue Scale (VAS), Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), PTSD Checklist for DSM-5 (PCL-5), and DN4 questionnaire, alongside physical tests (Lasègue’s sign, lateral bending test). Results: Post-intervention, participants demonstrated a statistically significant reduction in pain intensity (VAS: 7.5→3.9; p<0.001), depressive symptoms (PHQ-9: 13.7→9.0), anxiety symptoms (GAD-7: 11.3→8.0), neuropathic pain (DN4: 6.7→4.7), and PTSD severity (PCL-5: 37.5→28.9). Neuropathic pain of predominantly peripheral origin was identified in 100% of cases. Improvement in orthopedic symptoms was observed in 80% of patients. Discussion: These findings are consistent with current evidence regarding the complex neuropsychological interplay between chronic pain and PTSD. Short-term, structured psychotherapeutic support—even without psychopharmacological intervention—produced both statistically and clinically meaningful improvements in PHQ-9, GAD-7, and PCL-5 scores. The most prominent benefit was observed in physical pain and neuropathic components, likely reflecting the rapid effect of injection therapy and stabilization of the affective state. Limitations include the short follow-up period and lack of a control group, which restrict conclusions on long-term efficacy but provide compelling evidence of short-term benefit. Conclusions: An interdisciplinary approach combining local medical injections with short-term psychotherapeutic support effectively reduces pain, anxiety, depression, and PTSD symptoms in military personnel with chronic neuropathic pain. This program is feasible within military rehabilitation settings. Keywords: PTSD, chronic pain, military personnel, psychotherapy, neuropathic pain, analgesic injections, interdisciplinary approach, military rehabilitation.